El suicidio literario de Fernando Vallejo: La rambla paralela y la muerte como forma de protesta - Forero Gómez, Andrés (2024)
This article analyzes how Colombian writer Fernando Vallejo uses his novel La rambla paralela (2002) to expose his literary suicide (the death of his novelistic alter ego and his desire to stop writing altogether) as a form of protest towards the nonsensical nature of reality, which is frequently evidenced in Colombian society. To this end, the first section describes the role that suicide has had in Western thought and literature. Afterwards, the second section explains the reasons behind Vallejo’s critical stance in his works. Finally, the third and main section analyzes how Vallejo kills his narrative in his novel and how this act serves as the author’s most radical protest against contemporary reality.